Development of Passenger Air Carriers - Diminik, Igor; Pavlin, Stanislav; Novak, Doris (Promet - Traffic&Transportation)
The work presents the development of carriers in passengerair traffic, and the focus is on the development and operationsof carriers in chartered passenger transport. After the SecondWorld War, there were only scheduled air carriers. The need formass transport of tourists resulted in the development of chartercarriers or usage of scheduled carriers under different commercialconditions acceptable for tourism. Eventually also low-costcarriers appeared and they realize an increasing share in thepassenger transport especially in the aviation developed countries.